9514 1404 393
Answer:
g(f(7/3)) = 4 4/9
Step-by-step explanation:
g(f(7/3)) = g((7/3)²) = g(49/9) = 49/9 -1 = 40/9
g(f(7/3)) = 4 4/9
The expression 256 + 4 is equivalent to (200 + 4) + (40+4) + (16+4) according to distributive and commutative property of addition.
Given the expression 256 + 4. This can be solved using the partial sum expressed as:
256 + 4
256 + 4
= (200 + 40 + 16) + 4
According to the commutative property, A+B = B+A
The arrangement does not affect the result. Hence;
- (200 + 40 + 16) + 4 = 4 + (200 + 40 + 16)
Using the distributive law;
- 4 +(200 + 40 + 16) = (200 + 4) + (40 + 4) + (16 + 4)
Hence the expression 256 + 4 is equivalent to (200 + 4) + (40+4) + (16+4) according to distributive and commutative property of addition.
Learn more on partial sum here: brainly.com/question/6958503
Answer:
Tres respuestas posibles son:
2 y 3x^2 + x
2x y 3x + 2
x y 6x + 2
y hay muchas mas.
Step-by-step explanation:
Hay muchas respuestas posibles.
6x^2 + 2x = 2(3x^2 + x) = 2x(3x + 2) = x(6x + 2)
Answer:
Step-by-step explanation:
w=204.8
Ok so what do we know :
4 quarts = 1 gal
Julia has 4gal and 2 quarts or 18 quarts
ally has 12 quarts
so if julia has 18 quarts and ally has 12 that means that ally needs 6 more quarts (or 1gal 2 quarts) so that she and julia can have the same amount